Early Marriage: Understanding Motivations and Impact - Khodijah Khodijah; Bagong Suyanto; IB Wirawan (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2024)
This research aims to explore the dominant factors of early marriage from the other perspective of married teenage girls. This Research was conducted from May 2022 until January 2023 in Singosari, Malang. Purpose sampling was used to select 20 electable informants. Data was collected directly through semi-structured interviews and analyzed using conventional content analysis methods. This research uses a qualitative method with a content analysis design for exploring topics related to cultural context. The qualitative method with content analysis design in this study uses a traditional approach. The research results showed that multiple factors encourage the decision to marry at an early age from the perspective of adolescent girls including two categories namely